TBHP-mediated highly efficient dehydrogenative cross-oxidative coupling of methylarenes with acetanilides - Chen, Cui; Liu, Weibing; Zhou, Peng (Beilstein Journal of Organic Chemistry, 2016)
A TBHP-mediated dehydrogenative cross-oxidative-coupling approach has been developed for the synthesis of N-arylbenzamides from methylarenes and acetanilides. This cross-coupling method is free of transition metal catalysts and ligands, and no extra organic solvents are required, which make it an useful and attractive strategy for the straightforward construction of C–N bonds. Besides, this conversion is an important complement to the conventional C–N forming strategies.
Keywords: dehydrogenative cross oxidative coupling; methyl arenes; N-arylbenzamides; TBHP